LABORATORY STANDS FOR TESTING POWER EQUIPMENT (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2023)
This work is devoted to the analysis of the technical requirements for power equipment and stands for their testing, as well as the technical data on laboratory stands for the study of alternative energy sources, especially wind energy. Provides information about the temperature regime, taking into account the cooling medium. Standards for hydrogenerators are analyzed.